A Virtualization Architecture for Wireless Network Cards - Chandra, Ranveer (Cornell University Library, 2005)
This doctoral dissertation describes the design and applications of a new virtualization architecture for wireless network cards, called MultiNet. MultiNet virtualizes a single wireless card to appear as multiple virtual wireless cards to the user. Each virtual card can then be configured separately on a physically different network. The goal of MultiNet is to provide a user-level illusion of simultaneous connectivity on all virtual cards although the network card is on a single network at any instant. MultiNet achieves this transparency using intelligent buffering and switching algorithms. The switching and buffering mechanisms are implemented as a kernel driver, while the policies are implemented as a user-level service. The MultiNet system has been implemented over Windows XP and has been operational for over two years. It is agnostic of the upper layer protocols, and works well over popular IEEE 802.11 wireless LAN cards. Further, MultiNet enables a new class of applications, which were earlier only possible with multiple wireless cards in the device. This dissertation describes two such applications: Slotted Seeded Channel Hopping (SSCH) and Client Conduit. SSCH is a new channel hopping protocol that works over MultiNet, and utilizes frequency diversity to increase the capacity of IEEE 802.11 wireless networks. Each node using SSCH switches across channels in such a manner that nodes desiring to communicate overlap, while disjoint communications do not overlap, and hence do not interfere with each other. To achieve this, SSCH uses a novel scheme for distributed rendezvous and synchronization. Simulation results show that SSCH significantly increases network capacity in several multihop and single hop wireless networking scenarios. Client Conduit is a novel technique for providing connectivity to disconnected wireless clients with the help of nearby connected clients. It is based on MultiNet and takes advantage of the beaconing and probing mechanisms of IEEE 802.11 to ensure that connected clients do not pay unnecessary overheads while helping disconnected clients. Client Conduit has been implemented over Windows XP as part of an architecture for diagnosing faults in wireless networks.
Nominated by Cornell for the ACM best dissertation award Downloadable from: http://portal.acm.org/citation.cfm?id=1144933&dl=ACM&coll==&CFID=15151515&CFTOKEN=6184618